A Search for FDA Approved Drugs with Anti-ulcerative Effects: A computational Based Drug Repositioning Study - Abdulmajeed Yunusa1, Albashir Tahir1,2, Nura Abubakar1 (Sokoto Journal of Medical Laboratory Science)
Peptic ulcer disease (PUD) remains a significant global health concern, with millions affected annually. Current treatments, such as proton pump inhibitors and H2 receptor antagonists, face limitations like drug resistance and side effects. Drug repurposing, utilizing FDA-approved drugs, offers a cost-effective alternative to identify potential antiulcerative agents through computational methodologies. To evaluate the potential of FDA-approved drugs for antiulcerative effects by targeting key gastric receptors involved in acid secretion and gastrointestinal motility: Histamine 2 receptor (H2), Proton pump (PP), and Muscarinic 3 receptor (M3). This computational study utilized molecular docking and pharmacophore modeling techniques. Target proteins (H2, PP, M3) were selected from the Protein Data Bank. Drugs structurally related to known inhibitors were screened and docked using AutoDock Vina to assess binding affinities. Pharmacophores were developed using LigandScout for visualizing drug-receptor interactions. Binding scores and hydrogen bonding characteristics were analyzed to identify promising candidates. Cimetidine showed the strongest binding affinity (-7.4 kcal/mol) for H2 receptor, confirming its established therapeutic role. Other drugs, including Nifurtimox and Nitrofurantoin, demonstrated moderate affinities, suggesting potential for repurposing. For the M3 receptor, Dicyclomine exhibited the highest affinity (-9.6 kcal/mol), highlighting its robust interaction with gastrointestinal pathways. Pantoprazole displayed the strongest affinity (-7.3 kcal/mol), aligning with its role as a proton pump inhibitor. Rifabutin and Rifaximin showed moderate affinities with potential secondary effects on acid regulation. The study identified FDA-approved drugs with significant antiulcerative potential, demonstrating robust binding affinities to critical gastric receptors. These findings support drug repurposing as a promising strategy for PUD management. Experimental validation is recommended to confirm clinical efficacy.